Pain Acceptance Creates an Emotional Context That Protects against the Misuse of Prescription Opioids: A Study in a Sample of Patients with Chronic Noncancer Pain. - Esteve-Zarazaga, Rosa; Marcos, Estefanía; Reyes-Pérez, Ángela; López-Martínez, Alicia Eva; Ramírez-Maestre, María del Carmen (MDPI, 2021)
There is solid evidence of an association between several psychological flexibility processes, particularly pain acceptance, and adaptation to chronic pain. However, there are relatively few studies on the relationship between pain acceptance and opioid misuse in chronic pain patients. Thus, the aim of the present study was to test a hypothetical model in which pain acceptance would regulate pain sensations and pain-related thoughts and emotions, which would be related to opioid misuse. The sample comprised 140 chronic pain patients attending two hospitals. All patients were receiving pharmacological treatment, including opioid analgesics. Structural equation modelling analyses showed a significant association between higher pain acceptance and lower pain intensity and catastrophizing, and lower levels of anxiety and depression. Only higher anxiety and depression were significantly associated with increased opioid misuse. The results suggest that levels of anxiety, depression, and pain acceptance must be assessed before opioids are prescribed. Pain acceptance implies a relationship with internal events that protects against anxiety and depression and thus against opioid misuse. Acceptance and Commitment Therapy appears to be particularly appropriate for these patients.
Keywords: Dolor - Aspectos psicológicos; Opiáceos; Opioid prescriptions; Pain acceptance; Pain catastrophizing; Depression; Chronic pain; Misuse